2019
DOI: 10.1111/ehr.12878
|View full text |Cite
|
Sign up to set email alerts
|

A leader in an emerging new international market: the determinants of French wine exports, 1848–1938

Abstract: and participants at the American Association of Wine Economists Conference held in Bordeaux (2016), the workshop 'Crises et Changements dans les Campagnes Européennes' of the Ecole des Hautes Etudes en Sciences Sociales, Paris (2017), the Economic History Seminar of the University of Zaragoza ( 2018) and the workshop 'Wine Globalization: Past and Prospective' held in Adelaide (2018) for their help and advice. We also thank the editors and reviewers for their comments and suggestions.The usual disclaimers apply. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Theoretical and empirical studies have shown that there are many different factors that influence exports in general and wine exports in particular. Besides the gravity model, the literature indicates that there are other approaches to study the performance of wine exports, such as the export competitiveness of respective countries through indices of comparative advantage (Anderson, 2013), international diversification of firms through foreign direct investment (Outreville, 2016), and a historical perspective on the wine trade (Ayuda, Ferrer-Perez, and Pinilla, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretical and empirical studies have shown that there are many different factors that influence exports in general and wine exports in particular. Besides the gravity model, the literature indicates that there are other approaches to study the performance of wine exports, such as the export competitiveness of respective countries through indices of comparative advantage (Anderson, 2013), international diversification of firms through foreign direct investment (Outreville, 2016), and a historical perspective on the wine trade (Ayuda, Ferrer-Perez, and Pinilla, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tariff Commission, 1939). This increase in consumption was favored by modern marketing methods developed by quality wine producers (almost exclusively French) that included the use of modern advertising techniques, accreditation of the quality of their products and brands, adaptation to the preferences of the customers in different countries, the establishment of distribution networks, and a significant effort to improve the quality of their products (Guy, 2003;Simpson, 2011;Harding, 2017;Ayuda, Ferrer-Pérez, and Pinilla., 2019). Quality wine, particularly champagne, became a social marker of the emerging bourgeoisie (Guy, 2003;Harding, 2018;Desbois-Thibault, 2003).…”
Section: The Formation Of the International Wine Marketmentioning
confidence: 99%
“…This had two important consequences: first, the need to continue supplying the domestic market forced it to import large amounts of wine, which came mainly from neighboring countries, particularly Spain and also Italy; second, the shock also deeply affected French exports. Therefore, it was necessary to use wine from other countries to mix them with theirs to maintain them; furthermore, a profound process of export specialization in France of high-quality wines (mainly in bottles) began, which enabled the real value of exports to continue to increase until the end of the century; finally, the French difficulties facilitated a double process of substitution of exports in the low-quality segment by exports from other countries such as Spain or Italy, which attempted to steal their external markets and also by domestic production in the new producing countries (Ayuda, Ferrer-Pérez, and Pinilla, 2019). In the medium term, the initial replanting of French vineyards with highly productive hybrids that produced a wine with a low alcohol content and pale color, required the country to import wine with a higher alcohol content and a more intense color to mix it with and render it apt for consumption.…”
Section: The Formation Of the International Wine Marketmentioning
confidence: 99%
“…French demand even drove the construction of small railway spurs in Spain that connected the producing areas with the main lines enabling the wines to be transported to France. There is also empirical evidence of the positive impact that the reduction of the fleets had on France's wine exports (Ayuda et al, 2019).…”
Section: The Major Determinants Of Export Growthmentioning
confidence: 99%
“…Similarly, French wine exports between 1849 and 1938 were not driven by growth in the income per capita of their trading partners(Ayuda, Ferrer-Pérez and Pinilla, 2019).…”
mentioning
confidence: 97%